Composite coating with low-temperature radiation heat dissipation function as well as preparation method and application thereof

By using materials such as high-entropy rare earth phosphate and polyptyrene benzodioxazole nanofibers to prepare composite coatings, the shortcomings of existing infrared radiation coatings in terms of thermal conductivity and infrared emissivity are solved, and efficient low-temperature radiation heat dissipation is achieved and high electrical insulation.

CN119463685APending Publication Date: 2025-02-18FOSHAN XIANHU LAB

Patent Information

Application Number
CN202411419738.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing infrared radiation coatings have problems in terms of poor thermal conductivity, narrow infrared emissivity band range and are not suitable for low-temperature applications.

Method used

High-entropy rare earth phosphate and polyp-phenylbenzodioxazole nanofibers are used as the main preparation raw materials, combined with boron nitride, silicon carbide, silicon nitride and kaolin, and the composite coating is prepared by mixing acid treatment and ball milling steps to achieve High thermal conductivity, high insulation and high infrared radiation functions.

Benefits of technology

The infrared emission band is significantly widened, the infrared radiation performance of the material is improved at 2.5-15.4μm, and the thermal management needs of low-temperature electronic components are met, while maintaining high electrical insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463685A_ABST
    Figure CN119463685A_ABST
Patent Text Reader

Abstract

The invention discloses a composite coating with a low-temperature radiation heat dissipation function as well as a preparation method and application of the composite coating. The composite coating is prepared from the following raw material components in parts by weight: 10 to 20 parts of high-entropy rare earth phosphate, 5 to 10 parts of boron nitride, 3 to 5 parts of silicon carbide, 3 to 5 parts of silicon nitride, 2 to 5 parts of kaolin and 10 to 40 parts of poly (p-phenylene benzobisoxazole) nanofiber. According to the composite coating, the high-entropy rare earth phosphate and the poly (p-phenylene benzobisoxazole) nanofiber are used as main preparation raw materials, meanwhile, boron nitride, silicon carbide, silicon nitride and kaolin are added, and the high lattice distortion and low band gap of the high-entropy rare earth phosphate and the high heat conductivity and high insulation of the poly (p-phenylene benzobisoxazole) nanofiber are fully utilized; all the raw materials act together, so that the high thermal conductivity, high insulativity and high infrared radiation functions of the coating are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to a composite coating with low-temperature radiation heat dissipation function and a preparation method and application thereof. Background Art

[0002] With the popularization and application of miniaturized, high-efficiency and intelligent electronic components, their integration density and power density are also increasing. If the waste heat generated by these components is not dissipated in a timely and effective manner, it will not only cause the instability of the operation of electronic equipment, but also significantly shorten its service life, and may even cause safety hazards such as combustion or explosion. Infrared radiation heat dissipation technology provides a better solution for the thermal management of electronic components.

[0003] At present, infrared radiation coatings still have technical problems such as poor thermal conductivity, narrow wavelength range corresponding to infrared emissivity and unsuitability for low-temperature applications.

[0004] For example, the Chinese invention patent with publication number CN 10324910A discloses a radiation heat dissipation coating for reducing the junction temperature of LED chips and its preparation method. The heat dissipation coating with far-infrared ceramic powder, silicon carbide, cerium oxide, polymer resin, etc. as the main body can reduce the junction temperature of the LED, but the polymer resin used causes the thermal conductivity of the coating to be poor, and the thermal conductivity needs to be further enhanced.

[0005] The Chinese invention patent with publication number CN 115975453A discloses a flaky rare earth-based high-radiation heat dissipation coating, a preparation method and an application thereof. The obtained flaky rare earth-based high-radiation heat dissipation coating has an emissivity of 0.97 in the 8-13μm atmospheric window, but the infrared emissivity of the coating corresponds to a narrow band range, and the full-band high infrared emissivity is not ideal for heat dissipation of heat sources.

[0006] The Chinese invention patent with publication number CN 118126547A discloses a high-entropy cerate water-based paint and coating for high-temperature radiation heat dissipation, which has high infrared emissivity, directional heat conduction, strong toughness and a thermal expansion coefficient matching the substrate in the 1-20μm band. However, the paint is mainly used in high-temperature fields, while in the field of thermal management of low-temperature electronic components, high electrical insulation is also an important indicator of material performance. Summary of the invention

[0007] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a composite coating with low-temperature radiation heat dissipation function and a preparation method and application thereof, wherein the coating has both high infrared radiation performance and insulation performance, and can significantly broaden the infrared emission band, thereby improving the infrared radiation performance of the material at 2.5-15.4 μm.

[0008] To solve the above technical problems, the first aspect of the present invention provides a composite coating, whose raw material components include, by weight: 10-20 parts of high entropy rare earth phosphate, 5-10 parts of boron nitride, 3-5 parts of silicon carbide, 3-5 parts of silicon nitride, 2-5 parts of kaolin, and 10-40 parts of poly(p-phenylene benzobisoxazole) nanofibers.

[0009] Specifically, the composite coating of the present invention is prepared by high entropy rare earth phosphate, boron nitride, silicon carbide, silicon nitride, kaolin and poly (p-phenylene benzobisoxazole) nanofiber as raw materials, wherein: high entropy rare earth phosphate is more conducive to enhancing wide-band infrared radiation performance due to its high lattice distortion and low band gap compared to ordinary rare earth phosphate. At the same time, poly (p-phenylene benzobisoxazole) nanofiber is a kind of fiber material with high thermal conductivity and high insulation, and its theoretical axial thermal conductivity is up to 60W / mK, and it has high electrical insulation. The material not only has the function of reinforcing body, but also can be used as matrix material and functional particle composite. The composite coating of the present invention adopts poly (p-phenylene benzobisoxazole) nanofiber and high entropy rare earth phosphate with high infrared radiation performance, and adds boron nitride, silicon carbide, silicon nitride and kaolin at the same time, and each raw material acts together to achieve high thermal conductivity, high insulation and high infrared radiation function of the coating.

[0010] In some embodiments of the present invention, the chemical formula of the high entropy rare earth phosphate is APO4, wherein: the A position is at least four elements of La, Ce, Pr, Nd, Sm, and Yb.

[0011] In some embodiments of the present invention, among the elements at the A position, the La content is not lower than the average value of the remaining elements, and Ce, Pr, Nd, Sm, and Yb are in an equal molar ratio, thereby ensuring that the synthesized high-entropy rare earth phosphate is a monoclinic system to which LaPO4 belongs.

[0012] In some embodiments of the present invention, the particle size of the high entropy rare earth phosphate is less than 500 nm.

[0013] In some embodiments of the present invention, the particle size of the boron nitride is 100-300 nm.

[0014] In some embodiments of the present invention, the particle sizes of the silicon carbide and kaolin are both 200-500 nm.

[0015] In some embodiments of the present invention, the particle size of the silicon nitride is 400-600 nm.

[0016] A second aspect of the present invention provides a method for preparing the above-mentioned composite coating, comprising the following steps:

[0017] High entropy rare earth phosphate, boron nitride, silicon carbide, silicon nitride and kaolin are added to the first mixed acid and mixed; then poly(p-phenylene benzobisoxazole) nanofibers are added and ball-milled to obtain the composite coating.

[0018] In some embodiments of the present invention, the preparation steps of the poly(p-phenylene benzobisoxazole) nanofibers are: adding poly(p-phenylene benzobisoxazole) fibers to a second mixed acid and performing an acidification treatment to obtain the poly(p-phenylene benzobisoxazole) nanofibers; the second mixed acid has the same components as the first mixed acid, both including trifluoroacetic acid and methanesulfonic acid.

[0019] In some embodiments of the present invention, the volume ratio of trifluoroacetic acid to methanesulfonic acid is (0.5-1.5):1, and the preferred volume ratio is 1:1.

[0020] In some embodiments of the present invention, the acidification treatment time is 2-3 hours.

[0021] Specifically, the poly(p-phenylene benzobisoxazole) fibers are stripped into nanofibers by mixed acid treatment, which can retain the excellent mechanical and thermal properties of the poly(p-phenylene benzobisoxazole) fibers on the one hand, and form an efficient three-dimensional thermal conductive path on the other hand, thereby enhancing the thermal conductivity of the coating.

[0022] In some embodiments of the present invention, the mixing method is stirring at a rotation speed of 200-500 r / min for 20-40 min.

[0023] In some embodiments of the present invention, the ball milling medium is zirconia balls.

[0024] In some embodiments of the present invention, the process parameters of the ball milling are: ball milling at a rotation speed of 100-300 r / min for 6-12 hours.

[0025] The third aspect of the present invention provides a coating, which is formed by drying and heat-pressing the above composite coating.

[0026] In some embodiments of the present invention, the conditions for the hot pressing treatment are: hot pressing at 140-160° C. and a pressure of 5-15 MPa for 2-3 hours.

[0027] A fourth aspect of the present invention provides use of the above coating in electronic components, variable frequency motors or fuel cell stacks.

[0028] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:

[0029] (1) The composite coating of the present invention uses high entropy rare earth phosphate and poly(p-phenylene benzobisoxazole) nanofibers as main raw materials for preparation, and simultaneously adds boron nitride, silicon carbide, silicon nitride and kaolin, making full use of the high lattice distortion and low band gap of high entropy rare earth phosphate and the high thermal conductivity and high insulation of poly(p-phenylene benzobisoxazole) nanofibers. The raw materials work together to achieve high thermal conductivity, high insulation and high infrared radiation function of the coating.

[0030] (2) The present invention combines highly thermally conductive poly(p-phenylene benzobisoxazole) nanofibers with highly infrared radiative high-entropy rare earth phosphates, which can provide a continuous and efficient heat conduction channel for phonon transmission on the one hand; on the other hand, the high-entropy rare earth phosphate significantly broadens the infrared emission band by enhancing electron transitions, free carrier absorption, impurity energy level absorption and lattice vibration absorption, thereby improving the infrared radiation performance of the material in the range of 2.5-15.4 μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is an apparent image of the radiation heat dissipation coating prepared in Example 1;

[0032] Figure 2 The infrared emission spectra of the radiation heat dissipation coatings prepared in Example 1 and Comparative Example 1;

[0033] Figure 3 The thermal conductivity diagrams of the radiation heat dissipation coatings prepared in Example 1 and Comparative Example 2;

[0034] Figure 4 These are the resistivity test results of the radiant heat dissipation coatings prepared in Examples 1-6 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0035] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0036] Example 1

[0037] A method for preparing a radiation heat dissipation coating comprises the following steps:

[0038] (1) adding poly(p-phenylene benzobisoxazole) fibers to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) for acidification treatment for 2 hours to obtain poly(p-phenylene benzobisoxazole) nanofibers;

[0039] (2) By weight: high entropy rare earth phosphate (La 0.25 Ce 0.25 Pr 0.25 Nd 0.25 )PO4 20 parts, boron nitride 5 parts, silicon carbide 5 parts, silicon nitride 5 parts and kaolin 5 parts are added to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) and mechanically stirred at a speed of 300 r / min for 30 minutes; then 20 parts by weight of the poly(p-phenylene benzobisoxazole) nanofibers prepared in step (1) are added, and the whole is transferred to a planetary ball mill for ball milling (wherein: the ball milling medium is zirconia balls, the ball-to-material mass ratio is 3:1, the ball milling speed is 300 r / min, and the ball milling time is 6 hours) to obtain a composite coating;

[0040] (3) The composite coating prepared in step (2) is scraped onto the substrate, and dried and hot-pressed (hot-pressed at 150° C. and 10 MPa for 3 hours) to obtain the high-entropy rare earth phosphate insulating radiation heat dissipation composite coating of this embodiment.

[0041] Figure 1 This is the apparent image of the radiation heat dissipation coating prepared in Example 1. Figure 1 It can be seen that the coating has a uniform surface, a smooth thickness, and no obvious bubbles.

[0042] Example 2

[0043] A method for preparing a radiation heat dissipation coating comprises the following steps:

[0044] (1) adding poly(p-phenylene benzobisoxazole) fibers to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) for acidification treatment for 2 hours to obtain poly(p-phenylene benzobisoxazole) nanofibers;

[0045] (2) By weight: high entropy rare earth phosphate (La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 Sm 0.2 )PO4 20 parts, boron nitride 5 parts, silicon carbide 5 parts, silicon nitride 5 parts and kaolin 5 parts are added to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) and mechanically stirred at a speed of 400 r / min for 30 minutes; then 30 parts by weight of the poly(p-phenylene benzobisoxazole) nanofibers prepared in step (1) are added, and the whole is transferred to a planetary ball mill for ball milling (wherein: the ball milling medium is zirconia balls, the ball-to-material mass ratio is 3:1, the ball milling speed is 200 r / min, and the ball milling time is 9 hours) to obtain a composite coating;

[0046] (3) The composite coating prepared in step (2) is scraped onto the substrate, and dried and hot-pressed (hot-pressed at 150° C. and 10 MPa for 3 hours) to obtain the high-entropy rare earth phosphate insulating radiation heat dissipation composite coating of this embodiment.

[0047] Example 3

[0048] A method for preparing a radiation heat dissipation coating comprises the following steps:

[0049] (1) adding poly(p-phenylene benzobisoxazole) fibers to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) for acidification treatment for 2 hours to obtain poly(p-phenylene benzobisoxazole) nanofibers;

[0050] (2) By weight: high entropy rare earth phosphate (La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 Sm 0.2 )PO4 20 parts, boron nitride 10 parts, silicon carbide 3 parts, silicon nitride 3 parts and kaolin 5 parts are added to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) and mechanically stirred at a speed of 500 r / min for 40 minutes; then 20 parts by weight of poly(p-phenylene benzobisoxazole) nanofibers prepared in step (1) are added, and the whole is transferred to a planetary ball mill for ball milling (wherein: the ball milling medium is zirconia balls, the ball-to-material mass ratio is 3:1, the ball milling speed is 300 r / min, and the ball milling time is 9 hours) to obtain a composite coating;

[0051] (3) The composite coating prepared in step (2) is scraped onto the substrate, and dried and hot-pressed (hot-pressed at 150° C. and 10 MPa for 3 hours) to obtain the high-entropy rare earth phosphate insulating radiation heat dissipation composite coating of this embodiment.

[0052] Example 4

[0053] A method for preparing a radiation heat dissipation coating comprises the following steps:

[0054] (1) adding poly(p-phenylene benzobisoxazole) fibers to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) for acidification treatment for 2 hours to obtain poly(p-phenylene benzobisoxazole) nanofibers;

[0055] (2) By weight: high entropy rare earth phosphate (La 0.25 Ce 0.25 Pr 0.25 Sm 0.25)PO4 10 parts, boron nitride 10 parts, silicon carbide 5 parts, silicon nitride 5 parts and kaolin 5 parts are added to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) and mechanically stirred at a speed of 250r / min for 40min; then 25 parts by weight of poly(p-phenylene benzobisoxazole) nanofibers prepared in step (1) are added, and the whole is transferred to a planetary ball mill for ball milling (wherein: the ball milling medium is zirconia balls, the ball-to-material mass ratio is 3:1, the ball milling speed is 300r / min, and the ball milling time is 12 hours) to obtain a composite coating;

[0056] (3) The composite coating prepared in step (2) is scraped onto the substrate, and dried and hot-pressed (hot-pressed at 150° C. and 10 MPa for 3 hours) to obtain the high-entropy rare earth phosphate insulating radiation heat dissipation composite coating of this embodiment.

[0057] Example 5

[0058] A method for preparing a radiation heat dissipation coating comprises the following steps:

[0059] (1) adding poly(p-phenylene benzobisoxazole) fibers to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) for acidification treatment for 3 hours to obtain poly(p-phenylene benzobisoxazole) nanofibers;

[0060] (2) By weight: high entropy rare earth phosphate (La 0.6 Ce 0.1 Pr 0.1 Nd 0.1 Sm 0.1 )PO4 20 parts, boron nitride 10 parts, silicon carbide 5 parts, silicon nitride 5 parts and kaolin 5 parts are added to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) and mechanically stirred at a speed of 350r / min for 30min; then 30 parts by weight of poly(p-phenylene benzobisoxazole) nanofibers prepared in step (1) are added, and the whole is transferred to a planetary ball mill for ball milling (wherein: the ball milling medium is zirconia balls, the ball-to-material mass ratio is 3:1, the ball milling speed is 300r / min, and the ball milling time is 9 hours) to obtain a composite coating;

[0061] (3) The composite coating prepared in step (2) is scraped onto the substrate, and dried and hot-pressed (hot-pressed at 150° C. and 10 MPa for 3 hours) to obtain the high-entropy rare earth phosphate insulating radiation heat dissipation composite coating of this embodiment.

[0062] Example 6

[0063] A method for preparing a radiation heat dissipation coating comprises the following steps:

[0064] (1) adding poly(p-phenylene benzobisoxazole) fibers to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) for acidification treatment for 3 hours to obtain poly(p-phenylene benzobisoxazole) nanofibers;

[0065] (2) By weight: high entropy rare earth phosphate (La 0.4 Ce 0.2 Pr 0.2 Sm 0.2 )PO4 20 parts, boron nitride 5 parts, silicon carbide 3 parts, silicon nitride 3 parts and kaolin 2 parts are added to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) and mechanically stirred at a speed of 300 r / min for 30 minutes; then 20 parts by weight of the poly(p-phenylene benzobisoxazole) nanofibers prepared in step (1) are added, and the whole is transferred to a planetary ball mill for ball milling (wherein: the ball milling medium is zirconia balls, the ball-to-material mass ratio is 3:1, the ball milling speed is 300 r / min, and the ball milling time is 12 hours) to obtain a composite coating;

[0066] (3) The composite coating prepared in step (2) is scraped onto the substrate, and dried and hot-pressed (hot-pressed at 150° C. and 10 MPa for 3 hours) to obtain the high-entropy rare earth phosphate insulating radiation heat dissipation composite coating of this embodiment.

[0067] Comparative Example 1

[0068] A method for preparing a radiation heat dissipation coating comprises the following steps:

[0069] (1) adding poly(p-phenylene benzobisoxazole) fibers to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) for acidification treatment for 2 hours to obtain poly(p-phenylene benzobisoxazole) nanofibers;

[0070] (2) adding 5 parts by weight of lanthanum phosphate, 5 parts by weight of cerium phosphate, 5 parts by weight of praseodymium phosphate, 5 parts by weight of neodymium phosphate, 5 parts by weight of boron nitride, 5 parts by weight of silicon carbide, 5 parts by weight of silicon nitride and 5 parts by weight of kaolin to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) and mechanically stirring at a speed of 300 r / min for 30 min; then adding 20 parts by weight of the poly(p-phenylene benzobisoxazole) nanofibers obtained in step (1) and transferring the whole to a planetary ball mill for ball milling (wherein: the ball milling medium is zirconia balls, the ball-to-material mass ratio is 3:1, the ball milling speed is 300 r / min, and the ball milling time is 6 hours) to obtain a composite coating;

[0071] (3) The composite coating prepared in step (2) is scraped onto the substrate, and dried and hot-pressed (hot-pressed at 150° C. and 10 MPa for 3 hours) to obtain the radiant heat dissipation composite coating of this comparative example.

[0072] The difference between Comparative Example 1 and Example 1 is that the high entropy rare earth phosphate (La 0.25 Ce 0.25 Pr 0.25 Nd 0.25 )PO4 is replaced by the corresponding rare earth phosphate.

[0073] Comparative Example 2

[0074] A method for preparing a radiation heat dissipation coating comprises the following steps:

[0075] (1) By weight: high entropy rare earth phosphate (La 0.25 Ce 0.25 Pr 0.25 Nd 0.25 )PO4 20 parts, boron nitride 5 parts, silicon carbide 5 parts, silicon nitride 5 parts and kaolin 5 parts are added to a mixed acid (trifluoroacetic acid and methanesulfonic acid in a volume ratio of 1:1) and mechanically stirred at a speed of 300 r / min for 30 minutes; then the whole is transferred to a planetary ball mill for ball milling (wherein: the ball milling medium is zirconia balls, the ball-to-material mass ratio is 3:1, the ball milling speed is 300 r / min, and the ball milling time is 6 hours) to obtain a composite coating;

[0076] (2) The composite coating prepared in step (1) is scraped onto the substrate, and dried and hot-pressed (hot-pressed at 150° C. and 10 MPa for 3 hours) to obtain the radiant heat dissipation composite coating of this comparative example.

[0077] The only difference between Comparative Example 2 and Example 1 is that no poly(p-phenylene benzobisoxazole) nanofibers are added to the composite coating.

[0078] Performance Testing

[0079] 1. Infrared radiation performance

[0080] The radiation heat dissipation coatings prepared in Example 1 and Comparative Example 1 were tested using Fourier integrating sphere diffuse reflectance spectroscopy, with the spectral measurement range being 2.5-15.4 μm. The results are as follows: Figure 2 As shown in the figure, the horizontal axis Wavelength represents the wavelength, and the vertical axis Infrared emissivity represents the infrared emissivity. Figure 2 It can be seen that the coating of Example 1 has an emissivity of 0.952 in the 2.5-15.4 μm band, which has excellent infrared radiation performance, while the coating of Comparative Example 1 has an emissivity of 0.868 in the 2.5-15.4 μm band. This shows that compared with rare earth phosphates, the high lattice distortion and low band gap of high entropy rare earth phosphates greatly improve their wide-band emissivity.

[0081] 2. Thermal conductivity

[0082] The thermal conductivity of the radiative heat dissipation coatings prepared in Example 1 and Comparative Example 2 was tested by flash method, and the temperature test range was 25-375°C. The results are as follows: Figure 3 As shown, the horizontal axis Temperature represents temperature, and the vertical axis Thermal Conductivity represents thermal conductivity. Figure 3 It can be seen that the thermal conductivity of the coating in Example 1 is higher than 23W / m·K at 25-375℃, which is much higher than common polymer materials. The high thermal conductivity meets the heat dissipation requirements in the field of thermal management; and as the temperature increases, the thermal conductivity decreases at a low value, proving that it has high thermal stability. The thermal conductivity of the coating in Comparative Example 2 is lower than 5W / m·K at 25-375℃ because poly(p-phenylene benzobisoxazole) nanofibers are not added, the thermal conduction path is discontinuous, and boron nitride, silicon carbide, silicon nitride and kaolin thermal conductive functional particles cannot be efficiently connected, and the thermal conductivity is significantly lower than that of Example 1.

[0083] 3. Volume resistivity

[0084] The radiant heat dissipation coatings prepared in Examples 1-6 and Comparative Examples 1-2 were cut into rectangular samples of a certain size, electrodes were connected at both ends of the samples, voltage was applied through the electrodes, the current and voltage at both ends of the samples were measured, and the resistance value of the samples was calculated. Then the resistance value of the sample was divided by the volume of the sample to obtain the volume resistivity of the sample. The test results are shown in FIG. Figure 4 As shown. Figure 4 It can be seen that the volume resistivity (VolumeResistvity) of the radiation heat dissipation coatings prepared in Examples 1-6 and Comparative Example 1 is higher than 10 14 Ω·cm, with high electrical insulation. The volume resistivity of the radiation heat dissipation coating prepared in Comparative Example 2 is 2.1×10 12 Ω·cm, which is significantly lower than that in Example 1, further illustrating that the poly(p-phenylene benzobisoxazole) nanofibers have high electrical insulation properties.

[0085] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.

Claims

1. A composite coating, characterized in that: The raw material components include, by weight: 10-20 parts of high entropy rare earth phosphate, 5-10 parts of boron nitride, 3-5 parts of silicon carbide, 3-5 parts of silicon nitride, 2-5 parts of kaolin, and 10-40 parts of poly(p-phenylene benzobisoxazole) nanofibers.

2. The composite coating according to claim 1, characterized in that: The chemical formula of the high entropy rare earth phosphate is APO4, wherein the A position is at least four elements of La, Ce, Pr, Nd, Sm, and Yb.

3. The composite coating according to claim 1, characterized in that: The particle size of the high entropy rare earth phosphate is less than 500nm; and / or the particle size of the boron nitride is 100-300nm; and / or the particle sizes of the silicon carbide and kaolin are both 200-500nm; and / or the particle size of the silicon nitride is 400-600nm.

4. A method for preparing a composite coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: High entropy rare earth phosphate, boron nitride, silicon carbide, silicon nitride and kaolin are added to the first mixed acid and mixed; then poly(p-phenylene benzobisoxazole) nanofibers are added and ball-milled to obtain the composite coating.

5. The method for preparing the composite coating according to claim 4, characterized in that: The preparation steps of the poly(p-phenylene benzobisoxazole) nanofibers are as follows: adding poly(p-phenylene benzobisoxazole) fibers into a second mixed acid and performing an acidification treatment to obtain the poly(p-phenylene benzobisoxazole) nanofibers; the second mixed acid has the same components as the first mixed acid, both of which include trifluoroacetic acid and methanesulfonic acid.

6. The method for preparing the composite coating according to claim 5, characterized in that: The volume ratio of trifluoroacetic acid to methanesulfonic acid is (0.5-1.5):1; and / or, the acidification treatment time is 2-3 hours.

7. The method for preparing the composite coating according to claim 4, characterized in that: The mixing method is stirring at a rotation speed of 200-500 r / min for 20-40 min.

8. A coating, characterized in that The coating is formed by drying and heat-pressing the composite coating described in any one of items 1 to 3.

9. The coating according to claim 8, characterized in that The conditions of the hot pressing treatment are: pressing at 140-160° C. and using a pressure of 5-15 MPa for 2-3 hours.

10. Use of the coating according to claim 8 or 9 in electronic components, variable frequency motors or fuel cell stacks.

Citation Information

Patent Citations

  • Flaky rare-earth-based high-radiation heat dissipation coating as well as preparation method and application thereof

    CN115975453A

  • Anti-cracking inorganic thermal insulation coating material

    CN110054918A

  • High-entropy rare-earth phosphate powder and preparation method thereof

    CN110386595A

  • Preparation process of anti-wear and anti-corrosion coating for automobile chassis

    CN110423540A

  • Benzoxazole polymer nanofiber-based insulating and heat-conducting polymer composite material, and preparation method and application thereof

    CN113388249A

Cited By

  • Wave-absorbing high-entropy alloy composite coating and preparation method thereof

    CN120425337A